Early career researchers’ perspectives and roles in patient-oriented research - Rouleau, Geneviève; Bélisle-Pipon, Jean-Christophe; Birko, Stanislav; Karazivan, Philippe; Fernandez, Nicolas; Bilodeau, Karine; Chao, Yi-Sheng; de Pokomandy, Alexandra; Foley, Véronique; Gagnon, Bruno; Gontijo Guerra, Samantha; Khanji, Cynthia; et al. (Research involvement and engagement, 2018)
Plain English summary Patient-oriented research (POR) has received increasing attention in recent years. In this approach, patients’ experiential knowledge, derived from their experiences of living with a condition or illness and of interacting with the healthcare system, is recognized, valued, and seen as complementary to scientific knowledge. Early career researchers (ECRs) are the next generation of researchers, but little is known about how they perceive POR. In this study, ECRs were invited to reflect on what POR is, how patients can best contribute to research, and ECRs’ own role in developing POR. Using a technique designed to collect expert opinions and find consensus—the Delphi method—a panel of 16 ECRs responded, in three rounds, to three questionnaires, with the second and third being built on responses to the preceding ones. Based on their understanding, the panelists agreed that the most important element in defining POR would be valuing, mobilizing, and legitimizing the experiential knowledge of patients who live with a particular health condition. Panelists considered patients to be integral members of the research team, but were less convinced that they should be considered co-researchers. The panelists saw themselves as taking part in developing POR by sharing information, teaching, and encouraging POR among their peers, as well as by participating actively in organizations interested in POR. This is the first study to examine the perspectives of ECRs, who, along with many others, have an important role in supporting the on-going development of POR so that it becomes more widely adopted. Background Literature on patient-oriented research (POR) is growing rapidly. This field is increasingly encouraged by funders and structured by new research networks. POR involves moving away from considering patients as ‘subjects’, towards perceiving them as experts with experience-based knowledge. However, little is known about how early-career researchers (ECRs) perceive POR and their roles in developing it. This study examined how ECRs perceive POR, patients’ roles, the future of POR, and their own role in developing this approach. Methods A three-round Delphi study was conducted with Quebec’s Strategy for People and Patient-Oriented Research and Trials (SUPPORT) Unit awardees, composed of graduate students and clinicians, all ECRs. Of the 25 invited, 18 agreed to participate (72%), with a three-round retention rate of 89% ( n = 16 on 18). Panelists answered open-ended questions, selected the most salient statements, and rated their (dis)agreement with proposals using a 7-point scale. Results Five main themes emerged: 1) ECRs’ knowledge of and experience with POR; 2) the POR definition; 3) patients’ roles and contributions; 4) the future of POR; and 5) ECRs’ roles in POR development. This study revealed that the ECRs were not so familiar with POR, even given their opportunities for networking within a scholarship program. Panelists agreed on the main components of a POR definition: valuing, mobilizing, and legitimizing the experiential knowledge of patients living with a health condition; conducting research that focuses on patients’ concerns, participation, and outcomes; and integrating active partnership among a variety of actors. Panelists considered patients to be integral members of the research team (M = 5.31 ± 1.66), but were less convinced they should be considered co-researchers (M = 4.50 ± 1.75). Panelists saw themselves as playing many roles in developing POR, such as becoming well-informed about it and acting as knowledge brokers, motivators, doers, delegators, and activists. Conclusion The ECRs’ perspectives are informative on how the next generation of researchers envision POR, its future and how they might contribute to developing this approach. There is a clear need for a coherent and concerted strategy for POR capacity development, in which ECRs’ perspectives and their specific needs are taken into account.